Acceptability of assisted reproductive technologies in Hong Kong, a very low fertility Asian city. (30th September 2020) - Kim, J H; Wong, S Y S; Chan, R; Chan, R Y; Sumerlin, T S; Chan, L Y
Abstract: Background: Although advances in medical technologies now allow greater reproductive options, the social acceptance of assisted reproductive technologies (ART) has not been examined in East Asian countries which currently have the lowest fertility rates in the world and highly prohibitive regulations. Methods: A cross-sectional telephone surveys interviewed 990 among Hong Kong Chinese adults (>18 years of age) in 2015 who were asked about their knowledge and attitudes towards various ART and their inclination to use ART. A focus group was conducted (n = 30) on physicians to examine the perceived barriers and benefits of integrating ART as routine offerings. Results: Although nearly all adults (>92.0%) were familiar with ART procedures such as in vitro fertilization, sperm banking, and gestational surrogacy, attitudes supporting the use of these services and the inclination to use these services varied widely by socio-demographic attributes. Nearly one-third (31.5%) of women said that they would consider cryopreservation of their oocytes or embryos if they could afford it and 21.9% would encourage their female family members to do so. Although respondents considered sperm donation and embryo preservation to be well-accepted practices, support for these services was noticeably lower than in Western countries for unmarried individuals and homosexuals. Also, the vast majority of respondents were much more disinclined to use anonymous donor gametes than in Western countries. Among medical practitioners, the primary barriers to routine offering of these services to their clients was the perceived lack of cultural acceptance of these types of services. Conclusions: Public support of assisted reproductive services for genetic offspring is well-accepted for heterosexual couples. Main Messages: Asian countries with sub-replacement fertility levels may consider integrating ART into their mainstream health services and updating their regulatory frameworks. Key messages: Public support for assisted reproductive technologies is high for married couples only in Hong Kong. Given the sub-replacement fertility levels, cities in East Asia should consider updating regulatory frameworks to allow expansion of ART services.